2000
DOI: 10.1038/labinvest.3780134
|View full text |Cite
|
Sign up to set email alerts
|

Differentially Expressed Genes in Two LNCaP Prostate Cancer Cell Lines Reflecting Changes during Prostate Cancer Progression

Abstract: SUMMARY:Prostate cancer tends to become transformed to androgen-independent disease over time when treated by androgen-deprivation therapy. We used two variants of the human prostate cancer cell line LNCaP to study gene expression differences during prostate cancer progression to androgen-independent disease. Production of prostate-specific antigen was regarded as a marker of androgen-dependence and loss of prostate-specific antigen was regarded as a marker of androgenindependence. mRNA from both cell lines wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 27 publications
7
75
0
1
Order By: Relevance
“…It forms a complex with other proteins and is implicated in cell adhesion and growth inhibitory signals (Deblandre et al, 1995). The 1-8U is expressed in colitis-associated colon cancer and in severely inflamed mucosa in ulcerative colitis (Hisamatsu et al, 1999), as well as in an androgen-independent variant of the prostate carcinoma line LNCaP, but not in an androgen-dependent variant (Vaarala et al, 2000). Interestingly, 1-8D and 9-27 are induced by radiation in a p53-negative line, in an interferonindependent mechanism (Clave et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It forms a complex with other proteins and is implicated in cell adhesion and growth inhibitory signals (Deblandre et al, 1995). The 1-8U is expressed in colitis-associated colon cancer and in severely inflamed mucosa in ulcerative colitis (Hisamatsu et al, 1999), as well as in an androgen-independent variant of the prostate carcinoma line LNCaP, but not in an androgen-dependent variant (Vaarala et al, 2000). Interestingly, 1-8D and 9-27 are induced by radiation in a p53-negative line, in an interferonindependent mechanism (Clave et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…However, the LNCaP cell line has been derived from a lymph node metastasis of prostate cancer and the changes in expression detected in LNCaP cells are not comparable to the expression in prostate tissue in every case, as shown in our previous study. 5 Prostate cancer tissue is usually heterogeneous and the presence of androgen-independent clones with characteristics similar to those seen in androgen-independent LNCaP cells thus cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…5 Here we have extended the expression studies, using in situ hybridization and transcript quantification, to patient samples containing both benign prostate tissue and prostate cancer. Figure 1 shows prostatic expression of TMPRSS2 gene detected by in situ hybridization analysis in endocrine-treated and untreated prostate cancer patients.…”
Section: Expression Studies Of Tmprss2 Genementioning
confidence: 99%
See 1 more Smart Citation
“…FXYD-3 is a trans-membrane protein normally present in body tissues but overexpressed in several cancers. Increased expression in early tumour differentiation and tumour proliferation has indicated that it could possibly be used as a tumour marker (19,(71)(72)(73)(74)(75). There are also indications that FXYD-3 may be involved in tumour resistance to 5-FU chemotherapy (76).…”
Section: Study Imentioning
confidence: 99%